Process Synthesis: design for Improved Effectiveness - Duncan M Fraser (ASEAN Journal of Chemical Engineering, 2004)
This paper sets out the motivation for using process synthesis techniques that have been developed over the past 25 years. These techniques enable developing countries to design processes that bypass the incremental improvement route. The most developed aspects of process synthesis will be discussed with particular focus on pinch technology. The technology gives emphases on both energy and capital cost targets for heat exchanger networks (HENs) and on the design techniques developed to meet these targets. A retrofit path can be identified and costed to improve on an existing process, and yield a design target to meet specified investment limits. These techniques have been applied for use in mass exchange networks (MENs), water optimization, hydrogen and oxygen usage, and production scheduling. One of the most significant developments in these areas has been the impact diagram, which shows reduction in environmental impact versus investment. Use of these techniques willlead to processes that are more effective in their use of resources and are, therefore, more sustainable.